A review of muscle‐ and performance‐based assessment instruments in DM1. Issue 1 (1st March 2017) - Symonds, Tara; Campbell, Patrick; Randall, Jason A.
ABSTRACT: Introduction: Many outcome assessments used in myotonic dystrophy type 1 (DM1) were developed in other populations. Therefore, reliability and validity of these must be established in DM1 populations. Methods: A structured literature review was conducted to identify muscle strength and performance‐based functional outcome assessments used in DM1 and to review the DM1‐specific reliability and validity evidence for those outcome assessments. Results: Eighteen articles met inclusion criteria and were included in the review. The quantitative muscle testing technique and manual muscle testing were the key assessments of muscle strength. Reliability and validity evidence was also noted for several functional assessments of upper extremity (e.g., Purdue Pegboard Test) and lower extremity function (6‐Minute Walk Test). Conclusions: This review identified a few measures with encouraging reliability and validity for use in a DM1 populations but highlighted the need for more research. Muscle Nerve 56 : 78–85, 2017.